Community evidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission through air. (1st February 2021) - Lin, Guozhen; Zhang, Shiyu; Zhong, Yi; Zhang, Lin; Ai, Siqi; Li, Kuibiao; Su, Wenzhe; Cao, Lan; Zhao, Yuteng; Tian, Fei; Li, Jinrong; Wu, Yinglin; et al.
Abstract: Background: Nine COVID-19 (Corona Virus Disease, 2019) cases were observed in one community in Guangzhou. All the cases lived in three vertically aligned units of one building sharing the same piping system, which provided one unique opportunity to examine the transmission mode of SARS-CoV-2. Methods: We interviewed the cases on the history of travelling and close contact with the index patients. Respiratory samples from all the cases were collected for viral phylogenetic analyses. A simulation experiment in the building and a parallel control experiment in a similar building were then conducted to investigate the possibility of transmission through air. Results: Index patients living in Apartment 15-b had a travelling history in Wuhan, and four cases who lived in Apartment 25-b and 27-b were subsequently diagnosed. Phylogenetic analyses showed that virus of all the patients were from the same strain of the virus. No close contacts between the index cases and other families indicated that the transmission might not occur through droplet and close contacts. Airflow detection and simulation experiment revealed that flushing the toilets could increase the speed of airflow in the pipes and transmitted the airflow from Apartment 15-b to 25-b and 27-b. Reduced exhaust flow rates in the infected building might have contributed to the outbreak. Conclusions: The outbreak of COVID-19 in this community could be largely explained by the transmission through air, and future efforts to prevent the infection should take the possibility of transmission through air into consideration. A disconnected drain pipe and exhaust pipe for toilet should be considered in the architectural design to help prevent possible virus spreading through the air. Highlights: Provide evidence of SARS-CoV-2 transmission through air. Poor ventilation in the apartments increases the risk of transmission. Floor drain should be sealed with water and regular disinfected. The privately remodeled piping system might have played a role in this transmission.